Mold release film and method for manufacturing semiconductor package

By using a release film of a nitrile-containing (meth)acrylic polymer and other polymers, the problems of flow traces on the surface of the semiconductor package and the breakage of the release layer are solved, and high tensile properties and good release effect are achieved.

CN119522478APending Publication Date: 2025-02-25RESONAC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380055266.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2023-06-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When using a release film to perform semiconductor packaging molding, the surface of the packaging is prone to flow traces of the sealing material, and the stretchability of the release film is insufficient, resulting in the release layer being easily broken, affecting the release property of the package.

Method used

A release film containing at least 2 polymers, wherein at least 1 is a nitrile-containing (meth)acrylic polymer, and the difference in the SP value of the polymer is greater than or equal to 0.3, satisfying a specific component ratio and surface structure, such as a surface with a concave and convex shape, to improve tensile properties and reduce flow traces.

Benefits of technology

The sealing material flow traces on the surface of the semiconductor packaging are reduced, the tensile and mold release properties of the mold release film are improved, the breakage of the mold release layer is avoided, and the good appearance and mold release effect of the packaging are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522478A_ABST
    Figure CN119522478A_ABST
Patent Text Reader

Abstract

A mold release film comprising a mold release layer and a base material layer, the mold release layer comprising two or more types of polymers, and the mold release film satisfying at least one of (1)-(4). (1) The mold release layer has a plurality of types of regions having different component ratios, and when Raman spectroscopy is performed in the plurality of different types of regions, different peak intensities are exhibited in at least some of the plurality of different types of regions. (2) The surface of the mold release layer has a concave-convex shape, and when the convex and concave portions are subjected to Raman spectroscopy, at least a part of the convex portions and at least a part of the concave portions respectively exhibit different peak intensities. And (3) the difference between the SP values of at least two polymers is greater than or equal to 0.3. At least one of the (4) polymers is a nitrile group-containing (meth) acrylic polymer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a release film and a method for manufacturing a semiconductor package. Background Art

[0002] Semiconductor chips are usually sealed with resin to isolate and protect them from the outside air, and are mounted on a substrate as a molded product called a package. The molded product is made by injecting a sealing material containing resin into a mold. A plurality of cavities are provided in the mold, and the plurality of cavities are connected via a flow channel that serves as a flow path for the sealing material. In addition, in order to make it easy to release the molded product from the mold, research has been conducted on the structure of the mold, the addition of a release agent to the sealing resin, and the like.

[0003] On the other hand, due to the demand for miniaturization and multi-pin packaging, the ball grid array (BGA) method, the quad flat non-leaded (QFN) method, the wafer level chip size package (WL-CSP) method and other packages are increasing. In the QFN method, from the perspective of ensuring the stand-off and preventing the generation of burrs caused by the sealing material at the terminal part, and in the BGA method and the WL-CSP method, from the perspective of improving the demolding property of the package from the mold, a resin release film is arranged along the mold inside the mold, and the sealing material is injected into the mold to perform molding (for example, refer to patent document 1). The method of molding using a release film is called "film-assisted molding".

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2002-158242 Summary of the invention

[0007] Problems to be solved by the invention

[0008] When the release film is used, flow marks of the sealing material may remain on the surface of the package after molding, and the appearance may be deteriorated. In order to reduce the flow marks, it is considered to add fillers to the release layer of the release film.

[0009] In recent years, a technique of mounting a plurality of packages on a substrate and then sealing them together has been studied. In this case, since there are packages of various shapes on the substrate, excellent stretchability is required for the release film.

[0010] When the release film is stretched, the release layer also follows the stretching of the substrate, but the release layer may not follow the stretching completely and may break, so that the molded article cannot be released from the mold or is difficult to be released.

[0011] In particular, in a release film in which a filler is added to the release layer in order to reduce flow marks, the elongation of the release layer decreases and the release layer tends to be easily broken.

[0012] In view of such circumstances, an object of the present disclosure is to provide a release film having excellent stretchability and capable of reducing flow marks of a sealing material on the surface of a semiconductor package, and a method for manufacturing a semiconductor package using the release film.

[0013] Solutions to Solve Problems

[0014] Means for solving the above-mentioned problems include the following embodiments.

[0015] <1> A release film comprises a release layer and a substrate layer, wherein the release layer comprises two or more polymers, and the difference in SP values ​​between at least two of the polymers is greater than or equal to 0.3.

[0016] <2> A release film comprises a release layer and a substrate layer, wherein the release layer comprises two or more polymers, and at least one of the polymers is a nitrile group-containing (meth)acrylic polymer.

[0017] <3> A release film comprises a release layer and a base layer, wherein the release layer comprises two or more polymers and the release film satisfies at least one of the following (1) or (2).

[0018] (1) The release layer has a plurality of regions having different component ratios, and when Raman spectrometry is performed in the plurality of different regions, at least a portion of the plurality of different regions exhibits different peak intensities.

[0019] (2) The surface of the release layer has a concavo-convex shape, and when Raman spectrometry is performed on the convex portion and the concave portion, different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion, respectively.

[0020] <4> like <2> or <3> In the release film, the difference between the SP values ​​of at least two of the polymers is greater than or equal to 0.3.

[0021] <5> like <1> or <3> In the release film, at least one of the polymers is a nitrile group-containing (meth)acrylic polymer.

[0022] <6> like <1> or <2> The release film satisfies at least one of the following (1) or (2).

[0023] (1) The release layer has a plurality of regions having different component ratios, and when Raman spectrometry is performed in the plurality of different regions, at least a portion of the plurality of different regions exhibits different peak intensities.

[0024] (2) The surface of the release layer has a concavo-convex shape, and when Raman spectrometry is performed on the convex portion and the concave portion, different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion, respectively.

[0025] <7> like <3> or <6> The release film is characterized in that the component ratio of the polymer is different in at least a part of the different types of regions, or in at least a part of the convex part and at least a part of the concave part.

[0026] <8> like <7> The release film may include different contents of the nitrile group-containing (meth)acrylic polymer in at least a part of the different types of regions or in at least a part of the convex portion and at least a part of the concave portion.

[0027] <9> like <3> or <6> In the release film, at least a part of the protrusions and the recesses are formed by phase separation within the release layer.

[0028] <10> like <3> or <6> The release film described above is characterized in that, under a laser microscope, no interface is observed around the convex portion within the release layer.

[0029] <11> like <3> or <6> The release film, wherein the peak showing the different peak intensities is a peak derived from a nitrile group.

[0030] <12> like <3> or <6> The release film, wherein the surface of the release layer has a concavoconvex shape, and the peak intensity derived from the nitrile group in at least a part of the convex part is greater than the peak intensity derived from the nitrile group in at least a part of the concave part.

[0031] <13> like <3> or <6> The release film, wherein the surface of the release layer has a concavo-convex shape, and the content of the nitrile group-containing (meth)acrylic polymer in at least a portion of the convex portion is greater than the content of the nitrile group-containing (meth)acrylic polymer in at least a portion of the concave portion.

[0032] <14> like <1> to <13> The release film according to any one of the preceding claims, wherein an arithmetic mean roughness (Ra) of an outer surface of the release layer is less than or equal to 1.5 μm.

[0033] <15> like <1> to <14> The release film according to any one of the preceding claims, wherein the weight average molecular weight (Mw) of the polymer is greater than or equal to 1.0×10 5 .

[0034] <16> like <1> to <15> The release film according to any one of the preceding claims, wherein at least one of the polymers is a polymer containing a structural unit derived from a (meth)acrylonitrile monomer, and the difference in proportion of the structural unit derived from the (meth)acrylonitrile monomer between the at least two polymers is 1% by mass or more.

[0035] <17> like <1> to <16> The release film according to any one of the preceding claims, wherein the two or more polymers are (meth)acrylic polymers having a structural unit derived from a (meth)acryloyl monomer.

[0036] <18> like <1> to <17> The release film according to any one of the preceding claims, wherein at least a part of the polymer is cross-linked.

[0037] <19> like <1> to <18> The release film according to any one of the preceding claims, wherein the content of the polymer having the largest content in the release layer is 95% by mass or less relative to the total content of the polymers.

[0038] <20> like <1> to <19> The release film according to any one of the preceding claims, wherein the substrate layer is a polyester film.

[0039] <21> like <1> to <20> The release film according to any one of the preceding claims, wherein the release layer has a thickness of 1 μm to 50 μm.

[0040] <22> like <1> to <21> The mold release film according to any one of the preceding claims, wherein the mold release film is used for transfer molding or compression molding.

[0041] <23> A method for manufacturing a semiconductor package, wherein: <1> to <22> The release film described above is used to perform a transfer molding step or a compression molding step.

[0042] Effects of the Invention

[0043] According to the present disclosure, it is possible to provide a release film that has excellent stretchability and can reduce flow marks of a sealing material on the surface of a semiconductor package, and a method for manufacturing a semiconductor package using the release film. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] [ Fig. 1 ] is a schematic cross-sectional view showing the structure of a release film.

[0045] [ Fig. 2 ] are photographs and analysis diagrams of the surface of the release layer obtained using a laser microscope.

[0046] [ FIG. 3 ] is a spectrum result of component analysis of the discontinuous phase (island phase, convex part) and the continuous phase (sea phase, concave part) in sample G2 of FIG. 2 by micro-Raman spectroscopy.

[0047] FIG. 4 shows the spectral results of component analysis of the discontinuous phase (island phase, concave portion) and the continuous phase (sea phase, convex portion) in sample G3 of FIG. 2 by micro-Raman spectroscopy.

[0048] [ Fig. 5 ] is a plan view showing the shape of a test piece used for measuring the elongation at break of a release film. DETAILED DESCRIPTION

[0049] Hereinafter, the method for implementing the present disclosure is described in detail. However, the present disclosure is not limited to the following embodiments. In the following embodiments, except for the cases specifically indicated, the constituent elements (including element steps, etc.) are not necessary. The numerical values ​​and their ranges are also the same and do not limit the present disclosure.

[0050] In the present disclosure, the term "process" includes not only a process that is independent of other processes, but also a process that cannot be clearly distinguished from other processes as long as the purpose of the process can be achieved.

[0051] In the present disclosure, in a numerical range expressed using "~", the numerical values ​​described before and after "~" are included as the minimum value and the maximum value, respectively.

[0052] In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in one numerical range can also be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment.

[0053] In the present disclosure, each component may contain a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, the content or content of each component refers to the total content or content of the plurality of substances present in the composition unless otherwise specified.

[0054] In the present disclosure, the word "layer" includes not only a case where the layer is formed in the entire region when the region where the layer exists is observed, but also a case where the layer is formed only in a part of the region.

[0055] In the present disclosure, the thickness of the release film or each layer constituting the release film can be measured by a known method. For example, it can be measured using a micrometer or the like, or it can be measured based on a cross-sectional image of the release film. Alternatively, the material constituting the layer can be removed using a solvent or the like, and the thickness can be calculated based on the mass before and after removal, the density of the material, the area of ​​the layer, etc. When the thickness of the layer is not fixed, the arithmetic mean of the values ​​measured at any five points is taken as the thickness of the layer.

[0056] In the present disclosure, “(meth)acrylic acid” refers to either or both of acrylic acid and methacrylic acid, “(meth)acrylate” refers to either or both of acrylate and methacrylate, and “(meth)acryloyl” refers to either or both of acryloyl and methacryloyl.

[0057] In the present disclosure, when the embodiments are described with reference to the drawings, the configuration of the embodiments is not limited to the configuration shown in the drawings. In addition, the sizes of the components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.

[0058] <Release film>

[0059] The release film of the present disclosure includes a release layer and a base layer, wherein the release layer includes two or more polymers and the release film satisfies at least one of the following (1) to (4).

[0060] (1) The release layer has a plurality of regions having different component ratios, and when Raman spectrometry is performed in the plurality of different regions, at least a portion of the plurality of different regions exhibits different peak intensities.

[0061] (2) The surface of the release layer has a concavo-convex shape, and when Raman spectrometry is performed on the convex portion and the concave portion, different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion, respectively.

[0062] (3) The difference between the SP values ​​of at least two of the polymers is greater than or equal to 0.3.

[0063] (4) At least one of the polymers is a nitrile group-containing (meth)acrylic polymer.

[0064] In the present disclosure, "polymer" refers to a high molecular weight component that does not contain an organic filler. Here, the organic filler refers to an organic filler that is insoluble or poorly soluble in an organic solvent (e.g., toluene, methyl ethyl ketone, and ethyl acetate) that can be used to prepare a release layer forming composition. Here, being insoluble or poorly soluble in an organic solvent means that in a gel fraction test according to JIS K6769 (2013), the gel fraction after dispersing resin particles in an organic solvent such as toluene and maintaining at 50° C. for 24 hours is greater than or equal to 97% by mass.

[0065] In the present disclosure, “polymers of different types” means that the types of constituent monomers are different, or that the types of constituent monomers are the same but the content of structural units derived from at least one monomer differs by 1% by mass or more.

[0066] In the present disclosure, “displaying different peak intensities when performing Raman spectroscopy measurement” means that the intensity of a peak appearing at a certain position in a Raman spectrum obtained by Raman spectroscopy measurement is different, and the difference in the presence or absence of a peak at a certain position also includes the difference in peak intensity.

[0067] In the present disclosure, "convex portion" and "concave portion" refer to regions that are relatively high or low relative to other regions in the thickness direction. For example, a reference plane can be set as a concave portion and a region higher than the reference plane can be set as a convex portion. Alternatively, the reference plane can be set as a convex portion and a region lower than the reference plane can be set as a concave portion.

[0068] The mold release film of the present disclosure having the above-mentioned structure has excellent stretchability and can reduce flow marks on the surface of the semiconductor package after molding. The reason is not clear, but it is speculated as follows. It should be noted that the mold release film of the present disclosure is not limited by any of the following speculations.

[0069] As described in (1), by having a plurality of regions having different component ratios, and by having different peak intensities in at least a portion of the plurality of regions when Raman spectroscopy is performed in the plurality of regions, polymers are aggregated in one region to increase density, and local protrusions are formed, thereby forming a concavo-convex shape on the surface of the release layer. The existence of regions that each show different peak intensities when Raman spectroscopy is performed means that the component ratios of the regions that show different peak intensities are different from each other.

[0070] Furthermore, as described in (2), the surface of the release layer has a concavo-convex shape, which enables different peak intensities to be shown in at least a portion of the convex portion and at least a portion of the concave portion when Raman spectrometry is performed on the convex portion and the concave portion, respectively. Showing different peak intensities in at least a portion of the convex portion and at least a portion of the concave portion when Raman spectrometry is performed means that different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion when Raman spectrometry is performed. When there are multiple convex portions, the peak intensities of each convex portion may be the same or different. When there are multiple concave portions, the peak intensities of each concave portion may be the same or different.

[0071] Therefore, it is considered that the release film described in (1) or (2) can generate irregularities on the surface of the release film even without adding a filler to the release layer.

[0072] As one of the specific methods for forming multiple regions with different component ratios, as described in (3), two or more polymers having a difference in SP value of 0.3 or more are used. Polymers having a difference in SP value of 0.3 or more are separated from each other due to low compatibility, and polymers of the same kind coagulate with each other, so that release films of (1) and (2) can be obtained. In particular, as described in (4), when at least one of the polymers is a nitrile group-containing (meth)acrylic polymer, there is a tendency that the nitrile group-containing (meth)acrylic polymers are easily coagulated with each other to form convex portions.

[0073] In conventional release films, fillers are added to the release layer to make the surface of the release layer uneven, thereby reducing the flow marks of the sealing material on the surface of the semiconductor package. However, in such conventional release films, the release layer is easily broken starting from the filler. In addition, conventional release films are difficult to stretch because they contain fillers.

[0074] In contrast, in the release film of the present disclosure that satisfies at least one of (1) to (4), the surface can be made uneven even without adding a filler, so that it is not necessary to add a filler or the amount of filler can be reduced, resulting in excellent stretchability. In addition, the release film of the present disclosure has an uneven shape on the surface, so the flow marks of the sealing material on the surface of the semiconductor package are reduced.

[0075] It should be noted that the release film of the present invention has a concavo-convex shape on the surface, so the demoulding property is also excellent. Furthermore, in the release film of the present invention, it is not necessary to add fillers, so the occurrence of undesirable situations such as filler falling off can also be suppressed. Therefore, in the release film of the present invention, a convex portion in which a clear interface cannot be confirmed can also be formed. The convex portion in which a clear interface cannot be confirmed means that when observing with a laser microscope, the particle interface as when the filler is added cannot be confirmed.

[0076] As an example of the release film of the present disclosure, the cross-sectional structure of the release film is schematically shown in Figure 1. As shown in Figure 1, the release film 30 includes a substrate layer 10 and a release layer 20. The release film 30 may also have other layers. As other layers, a second release layer, an anchor enhancement layer, an antistatic layer, a coloring layer, etc. can be cited.

[0077] [Mold release layer]

[0078] The release layer contains at least two polymers.

[0079] The difference in SP values ​​of at least two polymers contained in the release layer is preferably greater than or equal to 0.3, more preferably greater than or equal to 0.5, and further preferably greater than or equal to 0.8. The upper limit of the difference in SP values ​​is not particularly limited, but is preferably less than or equal to 5.0, more preferably less than or equal to 4.0, and further preferably less than or equal to 3.0.

[0080] In the present disclosure, when there are two types of polymers contained in the release layer, the difference in SP value refers to the difference in SP value between the polymers. When there are three or more types of polymers contained in the release layer, the difference in SP value refers to the difference in SP value between the polymer with the highest SP value and the polymer with the lowest SP value among the polymers contained in the release layer.

[0081] The SP value is a solubility parameter derived from a part of the structural unit of a chemical structural formula, and is a value obtained by the Fedors method.

[0082] The type of polymer is not particularly limited, and is preferably selected in consideration of the adhesiveness, release properties, heat resistance, etc. of the release layer. Specifically, the polymer includes (meth)acrylic polymers, silicones, polyurethane polymers, etc. having a structural unit derived from a (meth)acryloyl monomer. At least one of the polymers is preferably a (meth)acrylic polymer, and more preferably two or more (meth)acrylic polymers are used.

[0083] The proportion of the (meth) acrylic polymer in the total polymer is preferably greater than or equal to 20% by mass, more preferably greater than or equal to 40% by mass, further preferably greater than or equal to 60% by mass, and may be greater than or equal to 80% by mass, greater than or equal to 85% by mass, greater than or equal to 90% by mass, or greater than or equal to 95% by mass. The upper limit is not particularly limited, and the proportion may be 100% by mass, less than or equal to 95% by mass, less than or equal to 90% by mass, or less than or equal to 85% by mass.

[0084] The (meth)acrylic acid polymer may be a homopolymer or a copolymer, and a homopolymer and a copolymer may be used together. At least one of the (meth)acrylic acid polymers is preferably a copolymer. The copolymer may contain a structural unit derived from a monomer A having no functional group, or a structural unit derived from a monomer B having a functional group.

[0085] Monomer A is preferably a monomer having a low glass transition temperature (Tg) (for example, less than or equal to -20°C). In addition, a monomer having a low Tg refers to a monomer having a low glass transition temperature when a homopolymer is synthesized using the monomer. Examples of monomer A include butyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. The copolymer may contain one structural unit derived from monomer A alone or two or more structural units may be contained in combination.

[0086] When the copolymer includes a structural unit derived from monomer A, the total content of the structural units derived from monomer A in the copolymer is preferably greater than 50% by mass, more preferably greater than or equal to 55% by mass, and further preferably greater than or equal to 60% by mass. In addition, the total content is preferably less than or equal to 99% by mass, more preferably less than or equal to 98% by mass, and further preferably less than or equal to 97% by mass.

[0087] At least one polymer is preferably a copolymer containing a structural unit from a monomer B having a functional group. As the functional group, carboxylic acid group, hydroxyl group, amide group, nitrile group, etc. can be mentioned. The functional group can be a crosslinking functional group or a non-crosslinking functional group. As the crosslinking functional group, carboxylic acid group, hydroxyl group, amide group, etc. can be mentioned, and as the non-crosslinking functional group, nitrile group, etc. can be mentioned. The copolymer can contain one structural unit from monomer B alone, or it can contain two or more in combination. At least one polymer is more preferably a (meth) acrylic polymer containing a nitrile group.

[0088] The crosslinking polymer having a crosslinkable functional group may be included in the release film by being at least partially crosslinked. In the present disclosure, a case where two or more polymers are crosslinked is also included in the form where the release film includes two or more polymers.

[0089] In the case where the polymer is cross-linked, the polymer before cross-linking can be analyzed or estimated by decomposing the bonds at the cross-linking points. For example, in the case where the polymer has a hydroxyl group and an isocyanate compound is used as a cross-linking agent, it can be estimated that a carbamate bond is formed to cross-link, and the carbamate bond can be selectively decomposed by pyridine.

[0090] The cross-linked polymer is preferably a cross-linked (meth)acrylic acid-based polymer, and preferably a cross-linked (meth)acrylic acid-based copolymer.

[0091] Examples of the monomer B1 having a crosslinkable functional group include (meth)acrylic acid, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, etc. Examples of the monomer B2 having a non-crosslinkable functional group include (meth)acrylonitrile, etc.

[0092] The total content of the structural units derived from the monomer B1 in at least one polymer is preferably greater than or equal to 0.1% by mass, more preferably greater than or equal to 0.5% by mass, and further preferably greater than or equal to 1.0% by mass. In addition, the total content is preferably less than or equal to 30% by mass, more preferably less than or equal to 25% by mass, and further preferably less than or equal to 20% by mass.

[0093] The total content of the structural units derived from the monomer B2 in at least one polymer is preferably greater than or equal to 1% by mass, more preferably greater than or equal to 3% by mass, and further preferably greater than or equal to 5% by mass. In addition, the content is preferably less than or equal to 40% by mass, more preferably less than or equal to 35% by mass, and further preferably less than or equal to 30% by mass.

[0094] At least one of the polymers is preferably a copolymer containing a structural unit derived from a monomer having a nitrile group, and more preferably a copolymer containing a structural unit derived from a (meth)acrylonitrile monomer. The polymer used in combination may be a homopolymer containing no structural unit derived from a monomer having a nitrile group, or may be a copolymer containing no structural unit derived from a monomer having a nitrile group.

[0095] In the copolymer containing the structural unit derived from the monomer having a nitrile group, the content of the structural unit derived from the monomer having a nitrile group is preferably greater than or equal to 1% by mass, more preferably greater than or equal to 3% by mass, and further preferably greater than or equal to 5% by mass. In addition, the content is preferably less than or equal to 40% by mass, more preferably less than or equal to 35% by mass, and further preferably less than or equal to 30% by mass.

[0096] In the copolymer containing the structural unit derived from the monomer having a nitrile group, the total content of the structural unit derived from the monomer A is preferably greater than or equal to 50% by mass, more preferably greater than or equal to 55% by mass, and further preferably greater than or equal to 60% by mass. In addition, the total content is preferably less than or equal to 94% by mass, more preferably less than or equal to 92% by mass, and further preferably less than or equal to 90% by mass.

[0097] In the copolymer containing the structural unit derived from the monomer having a nitrile group, the total content of the structural unit derived from the monomer B1 is preferably greater than or equal to 0.1% by mass, more preferably greater than or equal to 0.5% by mass, and further preferably greater than or equal to 1.0% by mass. In addition, the total content is preferably less than or equal to 30% by mass, more preferably less than or equal to 25% by mass, and further preferably less than or equal to 20% by mass.

[0098] In the copolymer not containing a structural unit derived from a monomer having a nitrile group, the total content of the structural units derived from the monomer A is preferably greater than or equal to 70% by mass, more preferably greater than or equal to 75% by mass, and further preferably greater than or equal to 80% by mass. In addition, the total content is preferably less than or equal to 99% by mass, more preferably less than or equal to 98% by mass, and further preferably less than or equal to 97% by mass.

[0099] In the copolymer not containing a structural unit derived from a monomer having a nitrile group, the total content of the structural units derived from the monomer B1 is preferably greater than or equal to 0.1% by mass, more preferably greater than or equal to 0.5% by mass, and further preferably greater than or equal to 1.0% by mass. In addition, the total content is preferably less than or equal to 30% by mass, more preferably less than or equal to 25% by mass, and further preferably less than or equal to 20% by mass.

[0100] In at least two polymers, the difference in the proportion of the structural unit derived from the (meth) acrylonitrile monomer is preferably greater than or equal to 1% by mass, more preferably greater than or equal to 3% by mass, and further preferably greater than or equal to 5% by mass. The upper limit of the difference in the proportion of the structural unit derived from the (meth) acrylonitrile monomer is not particularly limited, but is preferably less than or equal to 40% by mass, more preferably less than or equal to 35% by mass, and further preferably less than or equal to 30% by mass.

[0101] Examples of a preferred combination of two (meth)acrylic polymers include the following (I) and (II), and (I) is preferred.

[0102] (I) Combination of a (meth)acrylic polymer containing a nitrile group and a (meth)acrylic polymer not containing a nitrile group

[0103] (II) Both of the two types are nitrile group-containing (meth)acrylic polymers, and the contents of the structural units derived from the (meth)acrylonitrile monomer are different from each other.

[0104] The number average molecular weight (Mn) of the polymer may be, for example, greater than or equal to 1.0×10 3 , can be greater than or equal to 1.0×10 4 , can be greater than or equal to 1.0×10 5 , can be greater than or equal to 1.2×10 5 In addition, for example, it can be less than or equal to 1.0×10 6 , can be less than or equal to 5.0×10 5 .

[0105] The weight average molecular weight (Mw) of the polymer may be, for example, greater than or equal to 1.0×10 3 , can be greater than or equal to 1.0×10 4 , can be greater than or equal to 1.0×10 5 , can be greater than or equal to 3.0×10 5 , can be greater than or equal to 5.0×10 5 In addition, for example, it may be less than or equal to 5.0×10 6 , can be less than or equal to 1.0×10 6 .

[0106] The Mn and Mw of the polymer are measured by a common method using GPC (gel permeation chromatography).

[0107] The content of the polymer with the highest content in the release layer is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less relative to the total content of the polymer. When the content of the polymer with the highest content is 95% by mass or less, there is a tendency that unevenness is easily formed on the surface of the release film.

[0108] When the polymer is a cross-linked polymer, a cross-linking agent is preferably used. As the cross-linking agent, known cross-linking agents such as isocyanate compounds, melamine compounds, and epoxy compounds can be cited. In addition, from the viewpoint of forming a network structure that expands gently, the cross-linking agent is more preferably a multifunctional cross-linking agent such as a trifunctional or tetrafunctional cross-linking agent.

[0109] The isocyanate crosslinking agent is not particularly limited and can be selected from known compounds having isocyanate groups (isocyanate compounds). From the viewpoint of reactivity, bifunctional isocyanate compounds (compounds having two isocyanate groups) and polyfunctional isocyanates (compounds having three or more isocyanate groups) are preferred, and polyfunctional isocyanate compounds are more preferred.

[0110] Examples of the bifunctional isocyanate compound include aliphatic diisocyanate compounds, alicyclic diisocyanate compounds, aromatic diisocyanate compounds, carbodiimide-modified products of these diisocyanate compounds, and polymer compounds having these diisocyanate compounds in their molecules.

[0111] Examples of the aliphatic diisocyanate compound include 1,5-pentamethylene diisocyanate, 1,6-hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMHDI), lysine diisocyanate, and methyl norbornane diisocyanate (NBDI).

[0112] Examples of the alicyclic diisocyanate compound include trans-cyclohexane-1,4-diisocyanate, isophorone diisocyanate (IPDI), H6-XDI (hydrogenated XDI), and H12-MDI (hydrogenated MDI).

[0113] Examples of the aromatic diisocyanate compound include dimer acid diisocyanate, 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 1,4-phenylene diisocyanate, xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), tolidine diisocyanate (TODI), and 1,5-naphthalene diisocyanate (NDI).

[0114] Examples of the polyfunctional isocyanate compound include a trimer of a bifunctional isocyanate compound and a polymer compound having a trimer of a bifunctional isocyanate compound in a molecule.

[0115] Examples of the trimer of a bifunctional isocyanate compound include an isocyanurate form of a bifunctional isocyanate compound, an adduct of a bifunctional isocyanate compound, and a biuret form of a bifunctional isocyanate compound.

[0116] The content of the cross-linking agent contained in the release layer may be, for example, 0.1 to 50 parts by mass, or 1 to 40 parts by mass, relative to 100 parts by mass of the solid content of the polymer contained in the release layer.

[0117] The release layer may contain an anchor enhancer, a crosslinking accelerator, a colorant, an antistatic agent, etc. as required. For example, by making the release layer contain an antistatic agent, discharge is less likely to occur during peeling, and electrostatic damage to electronic components can be suppressed.

[0118] The release layer preferably has a plurality of regions having different component ratios, and when Raman spectrometry is performed in the plurality of different regions, at least a portion of the plurality of different regions respectively exhibits different peak intensities. In addition, the release layer preferably has a surface with a concave-convex shape, and when Raman spectrometry is performed in the convex portion and the concave portion, at least a portion of the convex portion and at least a portion of the concave portion respectively exhibit different peak intensities.

[0119] As an example, can enumerate at least a portion of different multiple regions or at least a portion of convex portion and at least a portion of recessed portion, the component ratio of polymer is different.As a more specific example, preferably at least a portion of different multiple regions or at least a portion of convex portion and at least a portion of recessed portion, the content of (methyl) acrylic polymer containing nitrile group is different.In addition, the peak showing different peak intensities is preferably the peak from nitrile group.

[0120] In the release layer, at least one region preferably contains a (meth) acrylic polymer containing a nitrile group, and in another region, a (meth) acrylic polymer containing a nitrile group may be contained or not contained. From the viewpoint of easily forming unevenness on the surface of the release layer, it is preferred that a (meth) acrylic polymer containing a nitrile group is not contained in another region. It should be noted that whether a (meth) acrylic polymer containing a nitrile group is not contained in a region can be confirmed by not detecting a spectral peak corresponding to the nitrile group when the region is subjected to component analysis using a micro Raman spectroscopy method described later.

[0121] When the surface of the release layer is observed in a planar manner, each region may be in a phase-separated state to form a continuous phase and a discontinuous phase. The area ratio of the continuous phase to the discontinuous phase can be adjusted by the mixing ratio of the polymer contained in the release layer. The polymer with a small content ratio in the release layer is contained in the discontinuous phase, and the polymer with a large content ratio is contained in the continuous phase.

[0122] In addition, it is preferred that the surface of the release layer has a concavo-convex shape, and the peak intensity derived from the nitrile group in at least a portion of the convex portion is greater than the peak intensity derived from the nitrile group in at least a portion of the concave portion. Furthermore, it is preferred that the surface of the release layer has a concavo-convex shape, and the content of the nitrile group-containing (meth) acrylic polymer in at least a portion of the convex portion is greater than the content of the nitrile group-containing (meth) acrylic polymer in at least a portion of the concave portion.

[0123] The Raman spectra of each region and the concavo-convex part are measured using a Raman spectrometer. As the Raman spectrometer, for example, "DXR2xi" manufactured by Thermo Fischer Scientific is used, and the measurement is performed under the following conditions.

[0124] Wavelength: 532nm

[0125] Output power: 10mW

[0126] Exposure time: 0.05 seconds

[0127] Scan times: 1000 times

[0128] Aperture: 25μm pinhole

[0129] Objective lens: 100 times

[0130] The ratio of components in each region and concave-convex portion can be measured by obtaining a spectrum of each portion irradiated with laser light using Raman spectroscopy. For example, the peak of the Raman spectrum of a specific component (such as nitrile group) constituting the release layer is identified in advance, and the relative content of the specific component in one portion and another portion is confirmed based on the signal intensity.

[0131] FIG2 is a photograph and an analysis diagram of the surface of the release layer obtained using a laser microscope. As a laser microscope, "VK-X3000" manufactured by KEYENCE Corporation was used, and observation was performed using a 50x objective lens. Although the above-mentioned laser microscope was used in FIG2 , the surface of the release layer may also be observed using other laser microscopes.

[0132] In FIG2 , sample G1 is a conventional mold release layer containing a filler, and samples G2 and G3 are mold release layers of the present disclosure that use a nitrile group-containing (meth) acrylic polymer (polymer A) and a nitrile group-free (meth) acrylic polymer (polymer B) in combination. In sample G2, the content of polymer A in all polymers is 15% by mass, and the content of polymer B is 85% by mass. In sample G3, the content of polymer A in all polymers is 85% by mass, and the content of polymer B is 15% by mass.

[0133] The first and second sections of FIG. 2 are planar photographs of the surface of the release layer when viewed in plan view, and the third section is a cross-sectional curve obtained by analyzing the concavo-convex shape of the surface using the straight line indicated by the arrow in the photograph of the second section.

[0134] As shown in FIG. 2 , in samples G2 and G3, the release layer is formed with a plurality of regions.

[0135] The content of the (meth) acrylic polymer containing nitrile groups in all polymers of sample G2 is less than half, in which case the area occupied by the convex portion in the entire surface is less than half. On the other hand, the content of the (meth) acrylic polymer containing nitrile groups in all polymers of sample G3 is greater than half, in which case the area occupied by the convex portion in the entire surface is greater than half. It can be seen from this that the content of the (meth) acrylic polymer containing nitrile groups in the convex portion is increased compared to the concave portion.

[0136] As shown in FIG. 2 , it can be seen that in the conventional sample G1, the filler is aggregated, and therefore the uniformity of the shape, size, etc. of the convex portion is low.

[0137] Fig. 3 is a spectrum result obtained by analyzing the components of the discontinuous phase (island phase, convex part) and the continuous phase (sea phase, concave part) in sample G2 of Fig. 2 by micro-Raman spectroscopy. Here, the discontinuous phase refers to a region with a small area in the observation surface, and the continuous phase refers to a region with a large area in the observation surface.

[0138] In Figure 3, a peak derived from a nitrile group was detected in the discontinuous phase (convex portion), whereas no peak derived from a nitrile group was detected in the continuous phase (concave portion). From this result, it can be seen that the component ratios of the polymers are different in the discontinuous phase (convex portion) and the continuous phase (concave portion). In addition, it can be seen that the content of the (meth)acrylic polymer containing a nitrile group is higher in the convex portion than in the concave portion.

[0139] Fig. 4 is the spectrum result obtained by component analysis of the convex part (sea phase, continuous phase) and concave part (island phase, discontinuous phase) in the sample G3 of Fig. 2 by micro-Raman spectroscopy. The peak from the nitrile group was detected in the convex part, while the peak from the nitrile group was not detected in the concave part. It can be seen from the result that the component ratio of the polymer is different in the convex part and the concave part. In addition, it can be seen that the content of the (meth) acrylic polymer containing the nitrile group is more in the convex part than in the concave part.

[0140] In Fig. 4, the nitrile group-containing (meth) acrylic polymer is contained as a main component in an amount of more than 50% by mass in all polymers to form a continuous phase, but the continuous phase forms a convex portion. In Fig. 3, the continuous phase forms a concave portion, but in Fig. 4, the opposite is true. However, in both cases of Fig. 3 and Fig. 4, the content of the nitrile group-containing (meth) acrylic polymer is greater in the convex portion than in the concave portion.

[0141] The thickness of the release layer is not particularly limited, but is preferably 1 μm or more, more preferably 3 μm or more, and further preferably 5 μm or more. When the thickness of the release layer is 1 μm or more, sufficient adhesion to the electronic component can be obtained, and the intrusion of the sealing material can be effectively suppressed.

[0142] The thickness of the release layer may be less than or equal to 50 μm, or less than or equal to 25 μm. When the thickness of the release layer is less than or equal to 50 μm, it is difficult to generate thermal shrinkage stress during thermal curing of the release layer, and it is easy to maintain the flatness of the release film. In addition, when the release film has a conductive layer, the distance between the surface of the release layer and the conductive layer will not be too far, the surface resistivity can be maintained low, and the electrostatic damage of the electronic components can be effectively suppressed.

[0143] Taking into account the ease of forming the release layer (coating properties, etc.), ensuring adhesive strength, etc., the thickness of the release layer is preferably 1 μm to 50 μm, more preferably 3 μm to 25 μm.

[0144] From the viewpoint of maximizing the effect of the embodiments of the present disclosure, the release layer preferably does not contain a filler, but may contain a filler. When a filler is used, it may be at least one of an organic filler and an inorganic filler. The content of the filler in the release layer may be, for example, less than or equal to 1% by volume, less than or equal to 0.5% by volume, or less than or equal to 0.1% by volume.

[0145] The content rate (volume %) of the filler in the mold release layer can be calculated based on the density measured by the Archimedean method and the specific gravity of the resin component and the filler.

[0146] (Elongation at break of release layer)

[0147] The elongation at break of the release layer is preferably greater than or equal to 100%, more preferably greater than or equal to 120%, and further preferably greater than or equal to 150%. Regarding the elongation at break of the release layer, for example, when the release layer contains at least one nitrile-containing (meth) acrylic polymer, it can be adjusted by the amount of the nitrile-containing (meth) acrylic polymer. The upper limit of the elongation at break of the release layer is not particularly limited, for example, it can be less than or equal to 800%, less than or equal to 500%, or less than or equal to 300%.

[0148] The elongation at break (%) of the release layer of the release film is measured as follows. First, a test piece of the shape shown in FIG5 is made using the release film. The two ends of the test piece are clamped with a testing machine to perform a tensile test. The measurement is carried out at 170°C and the tensile speed is 200 mm / min. Based on the distance A between the marks of the sample before the test (the length of the portion with a width of 10 mm of the test piece shown in FIG5: 40 mm) and the distance B between the marks when the release layer breaks, the elongation at break of the release layer is calculated by the following formula.

[0149] [Number 1]

[0150]

[0151] The breaking elongation of the release layer of the release film is measured by, for example, "Tensilon tensile tester RTA-100" manufactured by Orientec Corporation, "Tensilon universal tester RTG-1210" manufactured by A&D Corporation, or a similar tester having a clamping tool.

[0152] (Surface roughness of release layer)

[0153] The arithmetic mean roughness (Ra) of the outer surface (the surface opposite to the surface facing the substrate layer) of the release layer is preferably greater than or equal to 0.2 μm, more preferably greater than or equal to 0.25 μm, and further preferably greater than or equal to 0.3 μm. The upper limit of the arithmetic mean roughness (Ra) is not particularly limited, and may be, for example, less than or equal to 2.5 μm, less than or equal to 2.0 μm, less than or equal to 1.5 μm, or less than 1.0 μm.

[0154] The arithmetic mean roughness (Ra) of the outer surface of the release layer can be obtained by using a surface roughness measuring device (e.g., Kosaka Laboratory Co., Ltd., Model SE-3500) and analyzing the results under the conditions of a stylus tip diameter of 2 μm, a feed speed of 0.5 mm / s and a scanning distance of 8 mm according to JIS B 0601 (1994) or ISO 4287 (1997).

[0155] The arithmetic mean roughness (Ra) of the outer surface of the release layer can be adjusted by the mixing ratio of the polymer contained in the release layer, the thickness of the release layer, the amount of a crosslinking agent when a crosslinking agent is used, the amount of a catalyst when a catalyst is used, and the like.

[0156] [Base material layer]

[0157] The substrate layer is not particularly limited and can be appropriately selected from substrate layers used in the relevant technical field. From the viewpoint of improving the ability to follow the mold shape, it is preferred to use a substrate layer containing a resin having excellent stretchability.

[0158] Considering the heating temperature (about 100°C to 200°C) for molding the sealing material, it is desirable that the base material layer has heat resistance above the heating temperature. In addition, from the viewpoint of suppressing wrinkles and cracks when the release film is attached to the mold and when the sealing material flows, it is preferred to select the material of the base material layer in consideration of the elastic modulus and elongation during heating.

[0159] From the viewpoint of heat resistance and elastic modulus when heated, the material of the substrate layer is preferably a polyester resin. Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, and copolymers and modified resins thereof.

[0160] The substrate layer is preferably in a sheet shape, preferably a substrate layer obtained by molding a polyester resin into a sheet shape, more preferably a polyester film, and preferably a biaxially stretched polyester film from the viewpoint of mold followability.

[0161] The thickness of the substrate layer is not particularly limited, but is preferably 5 μm to 200 μm, and more preferably 10 μm to 100 μm. When the thickness is greater than or equal to 5 μm, there is a tendency that the workability is excellent and wrinkles are not easily generated. When the thickness is less than or equal to 200 μm, the mold followability is excellent during molding, so there is a tendency that wrinkles, etc. can be suppressed in the molded semiconductor package.

[0162] [Other components]

[0163] Depending on the material of the substrate layer, it is preferably designed to be easy to peel off the release sheet from the mold. For example, the surface of the substrate layer opposite to the release layer, that is, the surface of the substrate layer on the mold side, may be subjected to surface processing such as pear skin processing, or another release layer (second release layer) may be provided. The material of the second release layer is not particularly limited as long as it satisfies the requirements of release properties from the mold, heat resistance, etc., and the same material as the above-mentioned release layer (hereinafter also referred to as "specific release layer") can be used. The thickness of the second release layer is not particularly limited, but is preferably 0.1 μm to 100 μm.

[0164] Furthermore, an anchor enhancing layer, an antistatic layer, a colored layer, or the like may be provided between the specific release layer and the base layer, between the base layer and the second release layer, or the like, as necessary.

[0165] <Method for producing release film>

[0166] The release film of the present disclosure can be manufactured by a known method. For example, the release film of the present disclosure can be manufactured by applying a release layer forming composition to the substrate layer and drying it. The release layer forming composition includes at least two of the above-mentioned polymers, and may also include other resin components, and other components added as needed.

[0167] [Preparation of Release Layer Forming Composition]

[0168] The method for preparing the release layer forming composition is not particularly limited, and a known composition preparation method can be used. The solvent used in the preparation of the release layer forming composition is not particularly limited, and is preferably an organic solvent that can dissolve the polymer. Examples of the organic solvent include toluene, methyl ethyl ketone, ethyl acetate, and the like.

[0169] [Giving and drying]

[0170] The method for applying the release layer forming composition to the substrate layer is not particularly limited, and a known coating method such as a roll coating method, a rod coating method, a kiss coating method, etc. can be used. The amount of the release layer forming composition applied is preferably appropriately adjusted so that the thickness of the composition layer formed after drying is close to the thickness of the target release layer (e.g., 1 μm to 50 μm).

[0171] The method for drying the applied release layer-forming composition is not particularly limited, and a known drying method may be used. For example, a method of drying at 50° C. to 150° C. for 0.1 minute to 60 minutes may be used.

[0172] <Application of release film>

[0173] The mold release film of the present disclosure is used when a semiconductor chip is sealed with a sealing material. The mold release film of the present disclosure is preferably used for transfer molding or compression molding.

[0174] By using the release film of the present disclosure, it is possible to easily remove the semiconductor package (molded product) from the mold while suppressing damage to the semiconductor package. In addition, by using the release film of the present disclosure, it is possible to suppress flow marks of the sealing material on the surface of the semiconductor package (molded product), and the uniformity of the appearance is excellent. Furthermore, even when the release film is used under conditions requiring stretchability, the breakage of the release layer can be suppressed, so even in such a usage mode, the semiconductor package (molded product) can be easily removed from the mold while suppressing damage to the semiconductor package.

[0175] <Method for manufacturing semiconductor package>

[0176] In the method for manufacturing a semiconductor package disclosed herein, a transfer molding step or a compression molding step is performed using the release film of the present invention.

[0177] In the method for manufacturing a semiconductor package, first, the release film of the present disclosure is placed in a mold of a molding device so that the release film follows the shape of the mold. Examples of methods for making the release film follow the shape of the mold include vacuum adsorption.

[0178] Then, the semiconductor chip is sealed with a sealing material in the mold with the release film following it. The semiconductor chip is sealed with a sealing material in a state where the semiconductor chip and the release film are arranged in the mold, thereby manufacturing a semiconductor package. After manufacturing the semiconductor package, the mold is opened to take out the molded semiconductor package.

[0179] In the manufacturing method of the semiconductor package disclosed in the present invention, since the mold release film disclosed in the present invention is used, the flow traces of the sealing material on the surface of the semiconductor package can be suppressed, and a semiconductor package with excellent uniformity of appearance can be obtained. Furthermore, even if the mold release film is used under conditions requiring stretchability, the breakage of the mold release layer can be suppressed, so that the semiconductor package can be easily removed from the mold while suppressing damage to the semiconductor package.

[0180] Examples of the semiconductor chip used in the above method include semiconductor elements, capacitors, terminals, etc. The type of the sealing material used in the above method is not particularly limited, and examples thereof include resin compositions containing epoxy resins, acrylic resins, and the like.

[0181] Example

[0182] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited to these Examples.

[0183] (Synthesis of synthetic resins 1 to 4)

[0184] The monomers shown in the following Table 1 were copolymerized by solution polymerization using the blending amounts (parts by mass) shown in Table 1 to obtain synthetic resins 1 to 4.

[0185] The number average molecular weight Mn and the weight average molecular weight Mw of the obtained synthetic resins 1 to 4 were measured in terms of standard polystyrene by gel permeation chromatography (GPC).

[0186] Table 1 shows the SP values ​​of the obtained synthetic resins 1 to 4.

[0187] [Table 1]

[0188]

[0189] The monomers in Table 1 are as follows.

[0190] BA: Butyl acrylate

[0191] ·4-HBA: 4-Hydroxybutyl acrylate

[0192] MMA: Methyl methacrylate

[0193] ·2-HEA: 2-Hydroxyethyl acrylate

[0194] ·2-HEMA: 2-Hydroxyethyl Methacrylate

[0195] AN: Acrylonitrile

[0196] <Example 1>

[0197] With respect to 100 parts by mass of the total compounding amount of synthetic resin 1 (85 parts by mass) and synthetic resin 3 (15 parts by mass), 20 parts by mass of CORONATE L (trade name of Nippon Polyurethane Industry Co., Ltd.) as a crosslinking agent was added to toluene to prepare a toluene solution having a solid content of 15% by mass, and a release layer forming composition was prepared. As a substrate layer, a biaxially stretched polyethylene terephthalate film (Unitika Co., Ltd.: S-38) having a thickness of 38 μm was used and corona treated. Thereafter, a release layer forming composition was applied on one side of the substrate layer using a roll coater in such a manner that the average thickness after drying was 20 μm and dried to form a release layer, thereby obtaining a release film.

[0198] <Example 2>

[0199] A release film was produced in the same manner as in Example 1 except that the average thickness of the release layer after drying was 10 μm.

[0200] <Example 3>

[0201] A release film was produced in the same manner as in Example 1 except that the average thickness of the release layer after drying was 5 μm.

[0202] <Example 4>

[0203] A release film was prepared in the same manner as in Example 3 except that the synthetic resin 1 (90 parts by mass) and the synthetic resin 3 (10 parts by mass) were used.

[0204] <Example 5>

[0205] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was adjusted to 10 parts by mass based on 100 parts by mass of the total blending amount of the synthetic resin 1 (80 parts by mass) and the synthetic resin 3 (20 parts by mass).

[0206] <Example 6>

[0207] A mold release film was prepared in the same manner as in Example 3 except that the crosslinking agent was changed to 30 parts by mass relative to 100 parts by mass of the total blending amount of the synthetic resin 1 (80 parts by mass) and the synthetic resin 3 (20 parts by mass).

[0208] <Example 7>

[0209] A release film was prepared in the same manner as in Example 3 except that the synthetic resin 1 (50 parts by mass) and the synthetic resin 3 (50 parts by mass) were used.

[0210] <Example 8>

[0211] A release film was prepared in the same manner as in Example 3 except that the synthetic resin 1 (20 parts by mass) and the synthetic resin 3 (80 parts by mass) were used.

[0212] <Example 9>

[0213] A release film was prepared in the same manner as in Example 3 except that the synthetic resin 1 (10 parts by mass) and the synthetic resin 3 (90 parts by mass) were used.

[0214] <Example 10>

[0215] A release film was prepared in the same manner as in Example 3 except that the synthetic resin 1 (80 parts by mass) and the synthetic resin 4 (20 parts by mass) were used.

[0216] <Example 11>

[0217] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was changed to 30 parts by mass based on 100 parts by mass of the total blending amount of the synthetic resin 1 (80 parts by mass) and the synthetic resin 4 (20 parts by mass).

[0218] <Example 12>

[0219] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was adjusted to 20 parts by mass relative to 100 parts by mass of the total blending amount of the synthetic resin 1 (50 parts by mass) and the synthetic resin 4 (50 parts by mass).

[0220] <Example 13>

[0221] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was adjusted to 20 parts by mass relative to 100 parts by mass of the total blending amount of the synthetic resin 1 (20 parts by mass) and the synthetic resin 4 (80 parts by mass).

[0222] <Example 14>

[0223] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was adjusted to 2.2 parts by mass relative to 100 parts by mass of the total blending amount of the synthetic resin 3 (22 parts by mass) and the synthetic resin 4 (78 parts by mass).

[0224] <Comparative Example 1>

[0225] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was changed to 10 parts by mass based on 100 parts by mass of the total blending amount of the synthetic resin 1 (80 parts by mass) and the synthetic resin 2 (20 parts by mass).

[0226] <Comparative Example 2>

[0227] A release film was prepared in the same manner as in Example 3 except that the crosslinking agent was 40 parts by mass and the filler MX-500 (Soken Chemical Co., Ltd., trade name, acrylic plastic particles, average particle size 5 μm) was 15 parts by mass based on 100 parts by mass of the synthetic resin 2.

[0228] <Comparative Example 3>

[0229] A release film was prepared in the same manner as in Example 3 except that the cross-linking agent was changed to 10 parts by mass based on the synthetic resin 1 (100 parts by mass).

[0230] <Comparative Example 4>

[0231] A release film was prepared in the same manner as in Example 3 except that the cross-linking agent was changed to 20 parts by mass based on the synthetic resin 3 (100 parts by mass).

[0232] <Evaluation Test>

[0233] (Surface roughness of release layer (Ra))

[0234] The surface roughness (Ra) of the release layer of the release film was measured by the above method. The measurement was performed using a "surface roughness measuring instrument SE-3500" manufactured by Kosaka Laboratory Co., Ltd. The results are shown in Table 2.

[0235] (Elongation at break of release layer)

[0236] The elongation at break of the release layer at 170° C. was measured by the above method. The measurement was performed using “Tensilon Tensile Tester RTA-100 Model” manufactured by ORIENTEC CORPORATION. The results are shown in Table 2.

[0237] (Evaluation of EMC mold release properties)

[0238] As an index of the releasability of the release film from the sealing material after molding, the peeling force in a peeling test at a peeling angle of 180° and a peeling speed of 1000 mm / min was measured. The results were evaluated according to the following criteria. The results are shown in Table 2.

[0239] -Evaluation Criteria-

[0240] A: less than 150mN / 50mm

[0241] B: greater than or equal to 150mN / 50mm and less than 250mN / 50mm

[0242] C: greater than or equal to 250mN / 50mm

[0243] (Evaluation of release layer rupture)

[0244] A SUS plate (50 mm in width and 0.6 mm in thickness) was placed against the substrate layer side of the release film. Teflon (registered trademark) was placed on the release layer side, and a sealing material (Resonac Co., Ltd.: trade name "CEL-9750ZHF10") was spread between the release layer and Teflon. Furthermore, a heat and pressure treatment at 170°C and 12.6 MPa was performed for 5 minutes in a manner that the release layer side of the release film was in contact with the sealing material.

[0245] The molded package was cut with a "desktop manual cutter KPS-4002" manufactured by Sun Advance Co., Ltd. and cast with epoxy resin. The cast package was polished with abrasive paper of particle size P800, 1500, and 2200 to expose the cross section. The polished package cross section was observed with a "digital microscope VHX-7000" manufactured by KEYENCE Co., Ltd. to confirm whether the release layer was broken. The results are shown in Table 2.

[0246] (Evaluation of flow traces)

[0247] A sealing material (Resonac Co., Ltd.: trade name "CEL-9750ZHF10") was placed in contact with the release layer side of the release film, and a heat and pressure treatment was performed at 180°C and 32 MPa for 5 minutes. The package after the treatment was visually observed to confirm whether there were flow marks caused by the sealing material. The results are shown in Table 2.

[0248] [Table 2]

[0249]

[0250] The numerical values ​​of the synthetic resin, crosslinking agent and filler in Table 2 indicate the blending amounts (parts by mass).

[0251] As shown in the results of Table 2, the release films of Examples 1 to 14 had Ra values ​​equal to or higher than that of the release film of Comparative Example 2 to which a filler was added, and had an irregular shape on the surface.

[0252] As shown in the results of Table 2, the release films of Examples 1 to 14 were superior in stretchability, had no breakage in the release layer, and had good flow mark evaluation, compared with the release films of Comparative Examples 1 to 4.

[0253] Description of Reference Numerals

[0254] 10: Base material layer

[0255] 20: Adhesive layer

[0256] 30: Adhesive film.

Claims

1. A release film comprising a release layer and a substrate layer, wherein the release layer comprises two or more polymers, and the difference in SP values ​​between at least two of the polymers is greater than or equal to 0.

3.

2. A release film comprising a release layer and a substrate layer, wherein the release layer comprises two or more polymers, at least one of the polymers being a nitrile group-containing (meth)acrylic polymer.

3. A release film comprising a release layer and a substrate layer, wherein the release layer comprises two or more polymers, and the release film satisfies at least one of the following (1) or (2): (1) the release layer has a plurality of regions having different component ratios, and when Raman spectra are measured in the plurality of different regions, at least a portion of the plurality of different regions show different peak intensities, respectively; (2) The surface of the release layer has a concavo-convex shape, and when Raman spectrometry is performed on the convex portion and the concave portion, different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion, respectively.

4. The release film according to claim 2 or 3, wherein The difference between the SP values ​​of at least two of the polymers is greater than or equal to 0.

3.

5. The release film according to claim 1 or 3, wherein At least one of the polymers is a nitrile group-containing (meth)acrylic polymer.

6. The release film according to claim 1 or 2, which satisfies at least one of the following (1) or (2): (1) the release layer has a plurality of regions having different component ratios, and when Raman spectra are measured in the plurality of different regions, at least a portion of the plurality of different regions show different peak intensities, respectively; (2) The surface of the release layer has a concavo-convex shape, and when Raman spectrometry is performed on the convex portion and the concave portion, different peak intensities are shown in at least a portion of the convex portion and at least a portion of the concave portion, respectively.

7. The release film according to claim 3 or 6, wherein The component ratio of the polymer is different in at least a part of the different types of regions, or in at least a part of the convex portion and at least a part of the concave portion.

8. The release film according to claim 7, wherein The content of the nitrile group-containing (meth)acrylic polymer is different in at least a part of the different types of regions, or in at least a part of the convex portion and at least a part of the concave portion.

9. The release film according to claim 3 or 6, wherein At least a part of the protrusions and the recesses is formed by phase separation within the release layer.

10. The release film according to claim 3 or 6, wherein Under a laser microscope, no interface was observed around the protrusions within the release layer.

11. The release film according to claim 3 or 6, wherein The peak showing the different peak intensities is a peak derived from a nitrile group.

12. The release film according to claim 3 or 6, wherein The surface of the release layer has a concavoconvex shape, and the peak intensity derived from the nitrile group in at least a part of the convex part is greater than the peak intensity derived from the nitrile group in at least a part of the concave part.

13. The release film according to claim 3 or 6, wherein The release layer has a surface with projections and depressions, wherein the mass content of the nitrile group-containing (meth)acrylic polymer in at least a portion of the projections is greater than the mass content of the nitrile group-containing (meth)acrylic polymer in at least a portion of the depressions.

14. The release film according to any one of claims 1 to 13, wherein The outer surface of the release layer has an arithmetic mean roughness Ra of less than or equal to 1.5 μm.

15. The release film according to any one of claims 1 to 14, wherein The weight average molecular weight Mw of the polymer is greater than or equal to 1.0×10 5 .

16. The release film according to any one of claims 1 to 15, wherein At least one of the polymers is a polymer comprising a structural unit derived from a (meth)acrylonitrile monomer, In at least two of the polymers, the difference in the proportion of the structural unit derived from the (meth)acrylonitrile monomer is greater than or equal to 1 mass %.

17. The release film according to any one of claims 1 to 16, wherein The two or more polymers are (meth)acrylic polymers having a structural unit derived from a (meth)acryloyl monomer.

18. The release film according to any one of claims 1 to 17, wherein At least a portion of the polymer is cross-linked.

19. The release film according to any one of claims 1 to 18, wherein The content of the polymer with the largest content in the release layer is 95% by mass or less relative to the total content of the polymers.

20. The release film according to any one of claims 1 to 19, wherein The substrate layer is a polyester film.

21. The release film according to any one of claims 1 to 20, wherein The thickness of the demoulding layer is 1 μm to 50 μm.

22. The release film according to any one of claims 1 to 21, wherein The release film is used for transfer molding or compression molding.

23. A method for manufacturing a semiconductor package, wherein: A transfer molding process or a compression molding process is performed using the release film according to any one of claims 1 to 22.

Citation Information

Patent Citations

  • Mold release sheet for semiconductor mold and method for manufacturing resin-sealed semiconductor device

    JP2002158242A